Analisis Penerapan SAK EMKM pada Penyusunan Laporan Keuangan Usaha Mikro Kecil dan Menengah (Studi Kasus pada Toko Zahra Cake Pasaman) - Diva, Putri Para; Sumarni, Nini (Lembaga Yasin AlSys, 2026)
The implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM) in MSMEs has received attention in several studies, yet research that specifically discusses its application to the preparation of financial statements of culinary MSMEs in Pasaman Regency remains limited. This study aims to analyze the implementation of SAK-EMKM in the preparation of financial statements at Toko Zahra Cake Pasaman, identify the obstacles encountered, and determine the efforts made to overcome barriers to the application of these accounting standards. This study used a qualitative approach with a case study design, involving two main informants, namely the business owner and the financial manager, who were selected through purposive sampling. Data were collected through observation, unstructured interviews, and documentation, and were then analyzed using the interactive analysis technique of Miles and Huberman through the stages of data reduction, data display, and conclusion drawing. The results show that Toko Zahra Cake has not implemented SAK-EMKM optimally because financial recording is still carried out simply and is limited to recording cash receipts and cash disbursements, without preparing a statement of financial position, income statement, and notes to the financial statements in accordance with the standards. The main obstacles to implementing SAK-EMKM include low accounting understanding, limited human resources, lack of training related to SAK-EMKM, and the suboptimal separation of personal and business finances. This finding contributes to the development of signaling theory and broadens understanding of the implementation of SAK-EMKM in culinary MSMEs. The conclusion of this study emphasizes the importance of accounting understanding, separation of business finances, and continuous assistance for MSME actors in improving the quality of financial statements based on SAK-EMKM.